Implementasi Metode Zahrawain Dalam Pembelajaran Tahfidhul Qur’an Di Rumah Qur’an Al-Ummah Gresik Kota Baru - Chakimuddin, Mochammad; Amirudin, noor; Ladamay, Man Arfa' (Jurnal Mahasiswa Pendidikan, 2021)
Al-Ummah Qur'an House is one of the institutions prepared for generations of Islam to love the Qur'an and practice it by educating its students to memorize chapter 30 using the Zahrawain method. The Zahrawain method is used as a method of tahfidzul qur'an because it provides several easy, fast and durable ways to memorize the Qur'an for both children and parents. This research uses qualitative research with several data collection techniques, including: 1) observation, namely observing research objects or events in the form of humans, inanimate objects, and nature. 2) Documentation method, namely data collection method, by searching for data or information, which has been recorded/published in several existing documents, such as master books, personal books, and other certificates. 3) In-depth interviews in general, in-depth interviews are the process of obtaining information for research purposes. The results of data analysis showed that the implementation of the zahrawain method in the qur'an house, namely by means of talqin, meant that the teacher guided the children to imitate the readings that had been read by the teacher, one verse was read 3 times, then the second and third verses were also the same. The implementation of the Zahrawain Method at the Al-Ummah Qur'an House also includes the tasmi 'Listening method directly from the Ustadzah who guides him by reading one verse one by one until all students understand and memorize it. After everything is smooth in memorizing it will proceed to the next verse.